Tradisi Menyirih (Man Belo) dan Maknanya Bagi Masyarakat Karo di Desa Kutabuluh Kabupaten Karo - Dora, Nuriza; Azahra, Hafizza (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the betel habit (man belo) of the Karo people in Kutabuluh Village, Karo Regency, North Sumatra. Kutabuluh Village is one of the communities that maintains this tradition, which has been an integral part of their lives for centuries. The aim of this research is to reveal the meaning, function, and identify the challenges and obstacles faced by the community in maintaining the continuity of the betel tradition. This research uses a qualitative approach. The research method used is descriptive, data collection techniques used are observation, interviews and documentation with members of the betel community and traditional leaders. The research results reveal that the betel tradition has deep meaning in the culture of the Karo people, including as a means of communication, expression of togetherness, and embodiment of life values. Even though this tradition is facing pressure from social and economic changes, the Karo people in Kutabuluh Village remain committed to maintaining this tradition. The proposed solution involves public awareness campaigns, cultural education, collaboration with the government, and the creation of documentation materials to preserve and revive the betel tradition so that it remains relevant in the modern social and cultural context. It is hoped that this research can provide guidance for preserving this valuable cultural heritage and understanding its role in the lives of the Karo people.